Keputusan Pembelian Konsumen Pada “Warung Sederhana Gang Lebar, Wonocolo, Surabaya Di Kalangan Mahasiswa Uin Sunan Ampel Surabaya - Zahroh, Ma'rufatul; Nabila, Salma; Adawiyah, Robiatul; Anas, Fakhrizal; Faizah, Syarifah; Trisna Wahyudi, M. Adi (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Warung Sederhana is an eatery located in Gang Lebar, Wonocolo, Surabaya. Although there are many competitors, “Warung Sederhana remains the top choice among students. This study aims to analyze the factors that influence consumer purchasing decisions at “Warung Sederhana. The method used is a qualitative approach with a case study research type. Data was collected through interviews and observations. The results showed that the main factors that influence purchasing decisions are price, location, food quality, service, and recommendations from friends. Affordable prices and satisfying flavors are the main reasons students choose this shop. This research contributes to understanding consumer behavior in the micro business sector and can be a reference for stall owners in formulating more effective marketing strategies